Application of Local Microorganisms in the Composting Process using the Biopori Absorption Hole Method on the Content of Macro and Micronutrients - Aeni, Qurotul; Sumiyati, Sri; Sarminingsih, Anik (Universitas Diponegoro, 2024)
Organic waste can be used to make compost. One method of composting is by using Biopore Absorption Holes. Processing organic waste into compost can be done by adding local microorganisms (MOL) as bioactivators with varying MOL doses (0,25,50,175,100,125) % for every 5kg of food waste and vegetable waste categories. Composting process uses biopori absorption hole method with a depth of 80cm and diameter of 6 inches. MOL can be made from vegetable or fruit waste because the materials used are simple and easy to obtain. In the composting process, addition of MOL can increase the content of macro and micro nutrients. This research aims to determine the effect of reducing volume of compost and analyze the content of C, N, P, K, Fe, and Zn, from the composting process with different MOL doses and types of waste that have been determined. The research results showed that C, P, Fe and Zn tests had met the quality standards, while N and K tests had not met the quality standards. It can be concluded that the most effective activator dose is 25ml/L in food waste category because the compost produced meets the quality standards of SNI 19-7030-2004 concerning Compost Specifications from Organic Waste.